Comparative cranial grip force components in raccoon dog (Nyctereutes procyonoides) species from four ecologies: an index in diet resource partitioning (VETERINARIA, 2020)
This investigation studied maxillo-dental morpho-types in raccoon dogs (Nyctereutes procyonoides) from four different geographies in terms of cranial size and mandible morphology. It predicted cranial grip forces in canine and mandibular teeth regions (M2) with derived lever models and regression analysis to establish a possibility of diet-induced morphological changes in the skull construction in relation to ecological variations and geo-locations, adaptation to peculiar environmental markers in the species studied. Only comparisons between categories and models were utilized in this investigation. Based on cranial shape-size analysis, nine shape–size groups were developed from three shapes and sizes categories. Composite diet interaction patterns in the species were used to form cranial grip force predictions. Grip force was observed to have a direct proportionality with skull size and that very significant (p
Keywords: Skull morphology; Procyonidae biomechanics; odontology; adaptations